PATHOPHYSIOLOGICAL ASPECTS IN THE INTERACTION BETWEEN PERIODONTAL DISEASE AND DIABETES - Diana Anton; Irina-Georgeta Sufaru; Maria-Alexandra Martu; Raluca Mocanu; Georgeta-Maria Laza; Mihaela Maris; Silvia Martu; Luminita Lazar (Romanian Dental Association for Education, 2020)
Diabetes is a systemic disease with a number of major complications that can adversely affect quality of life. The disease is characterized by an increased susceptibility to infection, poor wound healing and increased morbidity and mortality associated with the evolution of the disease. Periodontal disease has been reported as the sixth complication of diabetes, along with neuropathy, nephropathy, retinopathy, and micro and macrovascular damage. Diabetes not only increases the risk and prevalence of periodontal disease, but also increases the progression of periodontal destruction. Both periodontal disease and diabetes have major inflammatory components. Not only is diabetes a risk factor for periodontitis, but periodontitis could also have a negative effect on glycaemic control.